1999
DOI: 10.1093/hmg/8.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of germline mutation spectra at the Huntington's disease locus supports a mitotic [correction of amitotic] mutation mechanism [published erratum appears in Hum Mol Genet 1999 Apr;8(4):717]

Abstract: Trinucleotide repeat disease alleles can undergo 'dynamic' mutations in which repeat number may change when a gene is transmitted from parent to offspring. By typing >3500 sperm, we determined the size distribution of Huntington's disease (HD) germline mutations produced by 26 individuals from the Venezuelan cohort with CAG/CTG repeat numbers ranging from 37 to 62. Both the mutation frequency and mean change in allele size increased with increasing somatic repeat number. The mutation frequencies averaged 82% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 67 publications
7
63
1
1
Order By: Relevance
“…Thus, their role in causing expansion is difficult to test. Further, tests of expansion among cell types have not always painted a consistent picture due to the fact that the effects of strand breaks cannot be separated from the effects of replication in proliferating cells [67][68][69][70][71][72][78][79][80]. However, the use of transgenic animals has been particularly informative [70,[80][81][82][83][84][85][86].…”
Section: Potential Mechanisms By Which Mmr Might Cause Cag Expansionmentioning
confidence: 99%
“…Thus, their role in causing expansion is difficult to test. Further, tests of expansion among cell types have not always painted a consistent picture due to the fact that the effects of strand breaks cannot be separated from the effects of replication in proliferating cells [67][68][69][70][71][72][78][79][80]. However, the use of transgenic animals has been particularly informative [70,[80][81][82][83][84][85][86].…”
Section: Potential Mechanisms By Which Mmr Might Cause Cag Expansionmentioning
confidence: 99%
“…Therefore, meiotic instability of the HD allele takes place during spermatogenesis (29). In the present study, by analyzing the pedigrees of patients, it was observed that 66% (10/15) of the individuals inherited the mutant allele paternally and 20% (3/15) inherited it maternally.…”
Section: Discussionmentioning
confidence: 50%
“…In the two largest cohorts (>250 parent-offspring pairs), the frequency of expansions was estimated to be 52.1% in a multiethnic HD population and 67.3% in the Dutch cohort, whereas only 18.1% and 25.2% contractions were observed, respectively [13,18]. For individuals carrying more than 49 CAG repeats, the mutation rates go up to >95% per generation [14,20]. In all cases, the frequency of expansions always exceeds the frequency of contractions in HD populations.…”
Section: Intergenerational Instabilitymentioning
confidence: 99%